Stimuli‐Regulated Enzymatically Degradable Smart Graphene‐Oxide‐Polymer Nanocarrier Facilitating Photothermal Gene Delivery. Issue 15 (17th May 2016) - Kim, Hyunwoo; Kim, Jinhwan; Lee, Minkyung; Choi, Hee Cheul; Kim, Won Jong
Abstract : Graphene oxide (GO) has attracted huge interest in the area of biomedical application due to its unique physicochemical properties, but the issue of long‐term toxicity in the body remains unclear. Here, the rationally designed GO nanocarriers (ssPEG‐PEI‐GO) modified with polyethylene glycol (PEG) and branched polyethylenimine (BPEI) via disulfide linkage are described to control the biological activity of GO as a delivery carrier and its degradation in biological systems. The ssPEG‐PEI‐GO efficiently interacts with plasmid DNA (pDNA) to form a stable nanocomplex by electrostatic interaction. After cellular uptake, ssPEG‐PEI‐GO/pDNA complex can easily escape from endosomes by photothermal conversion of GO upon near‐infrared irradiation and subsequent photothermally induced endosome disruption. After endosomal escape, reducing intracellular environment enables polymer dissociation and rapid gene release and therefore shows enhanced gene transfection efficiency with low toxicity in comparison with non‐reducible amide‐functionalized GO nanocarriers (amPEG‐PEI‐GO) and control BPEIs. Besides, dePEGylated GO nanocarrier, owing to its disulfide bond, exhibits higher entrapment by macrophages compared with amide‐functionalized one and subsequently degrades in macrophage. The degradation process can be monitored by photoluminescence emitted from degraded GO. These results suggest new directions in the design of biodegradable and multifunctional GO‐based nanocarrier for biomedical application. Abstract : A rationally designed graphene oxide nanocarrier with polyethylene glycol and branched polyethylenimine via disulfide linkage shows photothermally induced endosomal escape and gene release in a reducing intracellular environment. Enzymatic degradation of the nanocarrier in macrophages ensures its effective excretion. This strategy can be further applied in safe carbon‐based nanomedicine.